Asymptotic Stability of Index 2 and 3 Hesenberg Differential Algebraic Equations - H. Yasir, Kamal (Iraqi Journal of Science, 2023)
This paper aims to study the asymptotic stability of the equilibrium points of the index 2 and index 3 Hesenberg differential algebraic equations. The problem reformulated to an equivalent explicit differential algebraic equations system, so the asymptotic stability is easily investigated. The singular points such as impasse points and singularity induced bifurcation points are identified in this kind of differential algebraic equations by using conclusion of the explicit differential algebraic equations.